Case report of prune belly syndrome: An airway challenge too? (Indian Journal of Case Reports, 2024)
Prune belly syndrome (PBS) is a rare congenital disease presenting a characteristic triad of abdominal muscle deficiency, urinary tract abnormality, and cryptorchidism with associated anomalies of various systems. We report the anesthetic management of an infant with PBS with no obvious facial deformity in whom we encountered an unanticipated difficult airway. Multiple attempts to secure the airway with different supraglottic airway devices were unsuccessful and the trachea could be intubated only on the second attempt. The patient had deficient abdominal muscle and thus a prolonged duration of action of non-depolarizing muscle relaxant.